European female captives in Algiers, 1700-1809 - KERBACH , Belkacem; GHEZALI , Mohammed (La Revue d’Histoire Méditerranéenne, 2025)
This study aims to shed light on a topic that few studies have addressed in Algeria, particularly since most studies have addressed the issue of captives in a general manner. Many focused on male captives due to material availability on the subject. The personal memoirs of male captives were sufficient to cover the topic, unlike those of female captives, which were very few compared to those left by men. "between 1577 and 1704, historians counted 23 English captives who wrote about their captivity in North Africa," while only eight memoirs of female captives in North Africa were written in English during the Ottoman era, some of which were translated from other European languages. We believe that the topic of female captives has not received sufficient attention in Arab university curricula. Even studies in foreign languages have yet to significantly focus on the situation of Christian female captives in North Africa. Exceptions include a study by a Tunisian researcher published in French on "the condition of European female captives in Tunisia at the End of the 18th Century" and a study by Moroccan researcher Khalid El-Bekkoui titled "Female captives in North Africa..." in English. Research in this field still needs to be explored and requires further exploration